Act East policy and Northeast India - Datta, Sreeradha; Vivekananda International Foundation (New Delhi, India) (New Delhi Vitasta Publishing, 2021)
"India s Act East Policy hinges on development of the eight Northeast states with a view to achieving the foreign policy objective of enhancing ties with neighbouring countries. This book examines large infrastructure development across the region as it is seen pivotal for growth, employment and opening up of the local economy. It assesses the potential of cross-border trade with Myanmar and Bangladesh, some of which is a revival of traditional ties. It analyses how improving physical connectivity with the neighbours will establish direct linkages within the region and with the rest of India. It also gives an overview of government schemes and policies, investment fairs, tourism promotion efforts and the building of higher education institutions which will in due course transform the region. It is only when these come to fruition can the Northeast engage with the neighbours for prosperity in the region. "
Includes bibliographical references (pages 299-308) and index.
Keywords: Economic development; South Asian cooperation